Returns to Human Capital and Investment in New Technology - Luzio, Rodolfo (IMF Working Papers; Working Paper ;, 2001)
This paper presents a simple framework that illustrates the link between skill-based wage differentiation and human capital acquisition given skill-biased technical progress. The analysis points to the economic costs resulting from labor market and income redistribution policies that prevent the skill premium from playing its role in fostering human capital accumulation and the adoption of new technologies. The study compares key economic indicators among Canada, France, Germany, the United Kingdom, and the United States. Differences in wage differen-tiation and investment in new technologies among these countries could be related to policies affecting labor markets; such practices may reflect social choices.